Traditional children’s games: their relevance on skills development among rural Zimbabwean children age 3–8 Years - Madondo, Fortunate; Tsikira, Joseph (Routledge, 2022)
This study demonstrates the richness of traditional children’s games as an instructional tool for promoting holistic child development at the early childhood development (ECD) level. The study examines traditional children’s games from rural Zimbabwe. Valuable insights were drawn from different dimensions of indigenous knowledge systems, ranging from linguistics, crafts, cognitive skills, and clinical psychology. In this grounded theory study, participants included 10 ECD educators from rural schools in five selected Zimbabwean provinces. The researchers employed systematic random sampling technique. Data were generated using questionnaires, face-to-face interviews, and observations conducted in the five participating schools. The multiplicity of data generation methods enhanced validity of the data through triangulation. Findings suggested that traditional children’s games take cognizance of children’s socio-cultural context and are thus culturally relevant. The researchers recommend that ECD educators should maximize use of traditional children’s games in teaching. The skills that children develop in the classroom through cultural heritage resources like games are useful and sustainable in everyday life and the future.